The Influence Of Green Accounting, Financial Performance, And Company Size On Financial Sustainability - Pramastha, Tasha Asprilla; Sulistiyowati, Liliek Nur (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
The purpose of this study is to determine the effect of green accounting, financial performance, and firm size to determine the sustainability of manufacturing companies by paying attention to and maintaining the environment and public trust. This research uses Environmental, Social, Governance (ESG) as a proxy for green accounting, financial performance which is proxied by Return On Assets (ROA), Return On Equity (ROE), and Net Profit Margin (NPM), and firm size which is proxied by logarithms. from company size to Financial Sustainability which is proxied by the Debt to Equity Ratio (DER) in manufacturing companies listed on IDX. This research uses samples taken using a purposive sampling method and obtained 46 companies as samples and multiple linear regression analysis tools with data processing using SPSS version 20. The results of this research show that ROE has a positive and significant effect on financial sustainability, ESG and ROA have a significant negative effect on financial sustainability. Meanwhile, NPM and firm size have no influence on financial sustainability. Financial resilience is simultaneously influenced by ESG, ROA, ROE, NPM, and firm size when combined together.